La ciudad como sujeto: formas y procesos de su constitución moderna en Chile, siglos XVIII y XIX - Núñez, Andrés (Revista de Geografía Norte Grande, 2021)
This article analyzes the construction and the later consolidation of city's modern representation in Chile. This representation, in its enlightenment language, becomes a lecture event non comparable with other precedent urban and territories ¡maginaries, in the meantime it shows manifestations, procedures and particular meanings, all these structures of a temporal process, that lets the city to have its own singular history during the 18th and 19th centuries. The paper proposes the understanding of the city as a rationale figure and as a power and domain strategy, which had substantially collaborated in the configuration of Chile's current order and territorial sense. Given that, the city was, at the end, a production of truth